ANALGESICS ANTIPYRETICS IN PEDIATRICS - O.V. Zaitseva (Union of pediatricians of Russia, 2008)
The article considers one of the most critical issues in the pediatrics: the problem of children's hyperthermia. The article features the fever pathogenesis and 'points of application' for antipyretics, the data on efficiency and side effects of this group of medications, as well as indications to reduce heightened body temperature of children. The author demonstrates her own experience: an application of an antipyretic - ibuprofen.Key words: fever, antipyretics, medications of choice, medical indications, children.